Easy to draw monsters - Ho, Jannie; Cerato, Mattia (North Mankato, MN Picture Window Books, a Capstone Imprint, 2014)
Draw different kinds of monsters, including dragons, witches, and snakes
Arts (drawing)
1 2 13
NEW_ZTN_GN
Keywords: Drawing -- Technique -- Juvenile literature; Drawing -- Technique; Monsters in art -- Juvenile literature